Inhibition of localized corrosion in chromium containing stainless alloys - Rodríguez, Martín Alejandro (2012)
The application of stainless steels and chromium containing nickel-based alloys is limited by their susceptibility to localized corrosion in the forms of pitting and crevice corrosion or environmentally assisted cracking. Inhibitors may be normally found in service environments or added on purpose to mitigate or avoid the effects of aggressive agents such as chloride ions. The present study critically reviews the present knowledge on inhibition of chloride-induced pitting and crevice corrosion. Pioneering studies and recent findings are analyzed in light of the present theories for describing the localized corrosion processes. This review particularly focuses on the inhibition of crevice corrosion of alloy 22, which has been thoroughly studied in the past decade.